На задворках Великой империи: роман : в 2 кн. (В. С. Пикуль) - Пикуль Валентин Саввич (1992)
Экземпляры: аб. (2013) / Инвентарный номер: 49427 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 32 / ББК: 84(2Рос=Рус)6